2017
DOI: 10.3389/fmicb.2017.01088
|View full text |Cite
|
Sign up to set email alerts
|

Erythritol Availability in Bovine, Murine and Human Models Highlights a Potential Role for the Host Aldose Reductase during Brucella Infection

Abstract: Erythritol is the preferential carbon source for most brucellae, a group of facultative intracellular bacteria that cause a worldwide zoonosis. Since this polyol is abundant in genital organs of ruminants and swine, it is widely accepted that erythritol accounts at least in part for the characteristic genital tropism of brucellae. Nevertheless, proof of erythritol availability and essentiality during Brucella intracellular multiplication has remained elusive. To investigate this relationship, we compared ΔeryH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…It was argued that Brucella do not infect the human placenta because this organ does not contain erythritol (a carbon source for Brucella whose abundance in ruminant placenta is believed to be the reason for its placental tropism (Smith et al, 1962). However, it was shown that human fetal compartments (Jauniaux, Hempstock, Teng, Battaglia, & Burton, 2005), the fetomaternal blood (Brusati et al, 2005), and trophoblasts (Barbier et al, 2017) do contain erythritol. Moreover, isolation of Brucella from human placenta (Carpenter & Boak, 1931;Georghiou & Young, 1991;Grimaud, 1985;Janbon & Carderas De Kerleau, 1939;Messieri, 1936;Sarram, Feiz, Foruzandeh, & Gazanfarpour, 1974;Zowghi, Hedayeti, Ebadi, & Behroozikhah, 1996) provided unequivocal evidence that this organ is prone to infection.…”
Section: Consequences Of Brucella Infection On Trophoblast Functionsmentioning
confidence: 99%
“…It was argued that Brucella do not infect the human placenta because this organ does not contain erythritol (a carbon source for Brucella whose abundance in ruminant placenta is believed to be the reason for its placental tropism (Smith et al, 1962). However, it was shown that human fetal compartments (Jauniaux, Hempstock, Teng, Battaglia, & Burton, 2005), the fetomaternal blood (Brusati et al, 2005), and trophoblasts (Barbier et al, 2017) do contain erythritol. Moreover, isolation of Brucella from human placenta (Carpenter & Boak, 1931;Georghiou & Young, 1991;Grimaud, 1985;Janbon & Carderas De Kerleau, 1939;Messieri, 1936;Sarram, Feiz, Foruzandeh, & Gazanfarpour, 1974;Zowghi, Hedayeti, Ebadi, & Behroozikhah, 1996) provided unequivocal evidence that this organ is prone to infection.…”
Section: Consequences Of Brucella Infection On Trophoblast Functionsmentioning
confidence: 99%
“…Sexually mature and pregnant cows are thought to be more susceptible to brucellosis than sexually immature cattle of either sex (Adugna et al., 2013). This pattern might have been attributed to the affinity of this bacterial pathogen to the pregnant uterus, to erythritol in fetal tissue, and possibly to steroid hormones that are higher during pregnancy (Barbier et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that Brucella is a stealthy bacterium that can replicate massively inside the host cell without impacting its viability. In addition, such highly infected cells can be observed in vivo in different infection models such as alveolar macrophages of intranasally-infected mice 77 or trophoblasts of infected pregnant mice 78 or goats 79 .…”
Section: Discussionmentioning
confidence: 99%
“…At day 15 PF, mice were anaesthetised with isoflurane and sacrificed by cervical dislocation, as previously described in Barbier et al . 78 . All infections were performed at an Animal Biosafety Level 3 facility.…”
Section: Methodsmentioning
confidence: 99%